2009
DOI: 10.1021/cg801198p
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation Studies of Metal Oxide Nanowires

Abstract: Here, we report that the postsynthesis nitridation of tungsten oxide nanowires can result in single crystal nitride nanowires when the initial diameters of the nanowires are less than 10 nm. For nanowires with diameters greater than 10 nm, the nitridation of nanowires resulted in polycrystalline but highly oriented tungsten nitride domains in nanowires. Partially nitrided nanowires show an epitaxial relationship between the nitride nuclei and the oxide nanowire, being oriented with respect to the axial directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
(42 reference statements)
2
29
0
Order By: Relevance
“…Previous studies have demonstrated that the tungsten oxide nanowires can exhibit excellent field emission (FE) performances, which intrigues the researchers to explore their applications in cold‐cathode devices. Among various tungsten oxide nanostructures, the researchers found that the WO 2 nanowires exhibited the most excellent FE properties due to their high conductivity . On the other hand, for applications in large‐area cold‐cathode devices, such as X‐ray source and flat panel display, glass substrate is preferred due to its low‐cost and transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the tungsten oxide nanowires can exhibit excellent field emission (FE) performances, which intrigues the researchers to explore their applications in cold‐cathode devices. Among various tungsten oxide nanostructures, the researchers found that the WO 2 nanowires exhibited the most excellent FE properties due to their high conductivity . On the other hand, for applications in large‐area cold‐cathode devices, such as X‐ray source and flat panel display, glass substrate is preferred due to its low‐cost and transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Not a great deal of research has been done on phase transformation of 1D nanostructures. Recently, we showed that it is easy to transform oxides to nitrides and sulfides without compromising single crystallinity [36]. In the case of NWs, the diameter is on the order of nanometre scale, which is on the order of reaction diffusion length scale for many species, as shown in figure 5(a).…”
Section: Phase Transformation Of Nwsmentioning
confidence: 99%
“…But, if post-synthesis modifications can be performed easily in terms of doping, alloying and phase transformations, it is possible to extend the usefulness of the present technique beyond just making oxide nanostructures. Our recent work on nitridation using ammonia at elevated temperatures transformed the oxide NW arrays into nitride nanowire arrays without compromising the morphology and crystallinity [32]. Similar kind of easy post process modifications of the tungsten oxide material systems to others like carbides and sulfides can be done in presence of gas phase sources like CH 4 and H 2 S.…”
Section: Post-synthesis Transformation/modification Studiesmentioning
confidence: 99%